2012
DOI: 10.1016/j.cell.2012.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibition of BRDT for Male Contraception

Abstract: SummaryA pharmacologic approach to male contraception remains a longstanding challenge in medicine. Toward this objective, we explored the spermatogenic effects of a selective small-molecule inhibitor (JQ1) of the bromodomain and extraterminal (BET) subfamily of epigenetic reader proteins. Here, we report potent inhibition of the testis-specific member BRDT, which is essential for chromatin remodeling during spermatogenesis. Biochemical and crystallographic studies confirm that occupancy of the BRDT acetyl-lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
360
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(382 citation statements)
references
References 50 publications
15
360
2
5
Order By: Relevance
“…In the present study, we confirmed that intraperitoneal injection of JQ1 did not exert any adverse effect especially on normal bone [15,32]. A moderate increased bone mass was observed without affecting any bone strength parameters.…”
supporting
confidence: 86%
“…In the present study, we confirmed that intraperitoneal injection of JQ1 did not exert any adverse effect especially on normal bone [15,32]. A moderate increased bone mass was observed without affecting any bone strength parameters.…”
supporting
confidence: 86%
“…Although the pharmacologic properties of JQ1 are not ideal for in vivo studies (Matzuk et al 2012), we tested its activity against IDH2 mutant AML in vivo. Mice were transplanted with IDH2 R172K AML and, upon engraftment, treated (day 5) with vehicle or 50 mg/kg per day JQ1 by gavage for 2 wk (Filippakopoulos et al 2010;Zuber et al 2011b).…”
Section: Idh Mutant Amls Rapidly Differentiate In Response To Brd4 Inmentioning
confidence: 99%
“…Matzuk et al [6] discovered one such contraceptive target, the testis-specific and bromodomain-containing protein BRDT, and provided pharmacological validation of it as a target for male contraception. In our study, sAC was considered to be a potential contraceptive target, because it is located in the nucleus, mitochondria and microtubules [8], it is expressed in mammalian spermatozoa [9] and it is highly enriched in male germ cells [10].…”
Section: Discussionmentioning
confidence: 99%
“…To develop non-hormonal male contraceptives, developing small molecules that could target spermatogenesis-specific proteins that are essential for both sperm production and fertility in mammals appears attractive [5]. A selective small-molecule inhibitor (JQ1) of the testis-specific and bromodomain-containing protein BRDT is a good contraceptive agent targeting the male germ cells for contraception [6]. A short hairpin (sh)RNA aimed at silencing the expression of CatSper2, the key protein involved in rat sperm hyperactivation, is also considered to be a target for male contraception [7].…”
mentioning
confidence: 99%